2015
DOI: 10.3748/wjg.v21.i6.1938
|View full text |Cite
|
Sign up to set email alerts
|

Split-dose menthol-enhanced PEGvsPEG-ascorbic acid for colonoscopy preparation

Abstract: 4 L PEG plus menthol has better palatability and acceptability than 2 L ascorbic acid- PEG and is associated with a higher rate of excellent preparations; Clinicaltrial.gov identifier: NCT01788709.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Of these, 17 articles fulfilled the inclusion criteria and were finally included in the systematic review. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Studies characteristics are briefly reported in Table 1. All studies were published between 2008 and 2019.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…Of these, 17 articles fulfilled the inclusion criteria and were finally included in the systematic review. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Studies characteristics are briefly reported in Table 1. All studies were published between 2008 and 2019.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…In fact, the great majority of gastrointestinal cancers are preventable and curable through early diagnostic and therapeutic gastrointestinal endoscopy, and early screening combined with the resection of precancerous lesions has been confirmed to be an effective method to reduce the incidence and mortality ( 3 5 ). Currently, gastrointestinal endoscopy, endoscopic submucosal dissection, and endoscopic mucosal resection have become important methods for the diagnosis and treatment of gastrointestinal cancers because of their comparable safety ( 6 ), superior diagnostic sensitivity ( 7 ), facility of excision of early neoplastic lesions ( 8 ), cost-effectiveness, and minimal invasion ( 9 ) compared with the conventional surgical operation. However, unclear surgical fields caused by peristalsis and miss rates of 5%–32% for polyps remain concerns ( 10 ).…”
Section: Introductionmentioning
confidence: 99%